Hippocampal proteomics in a mice model of double stress during juvenile and adult stages. - Chaves-Peña, Patricia; Pérez-Martín, Margarita; Pedraza-Benítez, María del Carmen (Universidad de Málaga, 2026)
Proteomic analysis was performed on left hippocampal tissue from C57BL/6J mice subjected to different juvenile and adult stress paradigms and compared with control animals (CTRL). Experimental groups included mice exposed to juvenile stress (JS), adult stress (AS), or combined JS+AS, together with a control group. Hippocampi were collected at postnatal day 90 (PD90). Left hippocampi were homogenized in RIPA buffer, protein concentration was determined using the BCA assay, and samples were digested via gel-assisted proteolysis with trypsin. Peptide mixtures were analyzed by ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry (UHPLC-HRMS) using a Q-Exactive HF-X instrument (SCAI, Universidad de Málaga), acquiring MS/MS spectra for protein identification. Raw data were processed using Proteome Discoverer 2.5 and searched against the Mus musculus UniProt database (release 2025-02). A total of 3,850 high-confidence proteins were identified (FDR < 1%, ≥2 peptides, master proteins). Label-free quantification was performed using precursor ion intensities and normalized by total peptide amount. ANOVA identified upregulated proteins (p < 0.05 and log2 FC ≥ 1) and downregulated proteins (p < 0.05 and log2 FC ≤ −1) in the following comparisons: JS vs CTRL, AS vs CTRL, JS+AS vs CTRL, JS vs JS+AS, and AS vs JS+AS. Male and female datasets were analyzed separately. Raw proteomic data and volcano plots are available in RIUMA (Universidad de Málaga).
Keywords: Estrés (Fisiología); Hipocampo (Cerebro); Proteómica; Psicopatología; Hippocampus; Brain; Juvenile stress; Adult stress; Proteomics